Conductometric, spectrophotometric and thermodynamic studies of nickel sulfate in aqueous polyvinyl alcohol + methanol systems at different temperatures - Masood, Summyia; Saeed, Rehana; Ashfaq, Maria (European Journal of Chemistry, 2015)
The electrical conductance of nickel sulfate (NiSO4.6H2O) solutions in aqueous, aqueous polyvinyl alcohol (PVOH; 0.1, 0.5 and 0.9 g/dL), aqueous methanol (CH3OH) system (30%, v:v) and aqueous PVOH+CH3OH systems were measured in the concentration ranges 0.4×10-2 to 10×10-2 mol/L, at different temperatures (298, 303, 308, 313 and 318 K). Ionic interactions of nickel sulfate in aqueous and mixed solvent systems were measured by conductometric analysis. Different relations were used to evaluate conductometric data, for the calculation of molar conductance, molar conductance at infinite dilution (Ʌ°m), degree of dissociation (a), dissociation constant (Kd) and Walden product. The increased in Ʌ°mvalues with the increase in percent composition of aqueous PVOH, show that PVOH interaction with solvents (water and methanol) was higher as compare to PVOH interaction with NiSO4. Solvent effect was also studied by spectrophotometric analysis of NiSO4 in aqueous, aqueous PVOH and aqueous PVOH + CH3OH system. Thermodynamic parameters for dissociation process such as energy of activation (Ea#), free energy change of activation (ΔGd#), enthalpy change of activation (ΔHd#), and entropy change of activation (ΔSd#) were also calculated as a function of temperature and solvent composition.